La verdad los hará libres frente a las propuestas de reconciliación de los obispos argentinos - Mariano Fabris (Nuevo mundo - Mundos Nuevos, 2025)
The objective of this contribution is to reflect on the relationship between the volumes that make up La verdad los hará libres and an extensive history of interventions by the Catholic Church articulated around the idea of reconciliation. We are particularly interested in establishing dialogues with that particularly productive juncture in the elaboration of revisions of the past, which was the transition to democracy. We consider that La verdad los hará libres, on the one hand, fits into that trajectory of interventions in a way that can be read as one of the forms that the Church’s participation in current debates about the dictatorial past takes. But, on the other hand, it constitutes a break from that same trajectory by turning the interventions of the Church and its hierarchy into an object of analysis. We understand that this coexistence in the same text of ruptures and continuities could be associated with a tension that runs through its pages, sometimes explicitly, between memory and history.